The composition and structure of the microcrustacean zooplankton of the artificial reservoir Grliško in Eastern Serbia - Ninić Ljiljana; Nikolić Vera; Đikanović Vesna; Miličić Dragana (Kragujevac Journal of Science, 2023)
This paper provides an overview of the qualitative composition and structure of the microcrustacean of the Grliško reservoir based on field research conducted from 11 June 2019 to 9 July 2019. Sampling was carried out every seven days at sub-sites with different macrofauna, using the standard hydrobiological methodology. A total of 18 zooplankton taxa were recorded, belonging to the following groups: Rotifera (1 taxon), Cladocera (12 taxa), and Copepoda (5 taxa). The largest number of taxa was found in June. The total number of taxa was almost the same in the sub-areas with a lot of macrovegetation and without vegetation but differed in the qualitative composition of zooplankton species, spatially and temporally. Since the main purpose of the Grliško reservoir is to provide water for the population, it is necessary to constantly monitor the zooplankton, as it can be an important indicator of the state of this aquatic ecosystem.